Forest ecology and conservation a handbook of techniques - Newton, Adrian C. (Oxford Oxford University Press, 2007)
"Forest Ecology and Conservation describes research methods and techniques relevant to understanding forest ecology, with a particular focus on those that are relevant to practical conservation and sustainable forest management. This information is currently disparate and difficult to locate and, as with other books in this series, the intention is to provide a comprehensive synthesis. Methods are presented for assessing forest extent and condition, structure and composition, and forest dynamics at a variety of scales. Particular emphasis is given to state-of-the-art techniques such as remote sensing, GIS, computer modelling and molecular markers. However, traditional methods of forest mensuration and ecological survey are also presented." "This book will be particularly relevant to postgraduate and advanced undergraduate students, as well as established researchers in the fields of ecology, conservation biology and environmental management. It will also be a valuable reference for conservation practitioners, land managers, and forest professionals worldwide."--BOOK JACKET.
Forest extent and condition -- Forest structure and composition -- Understanding forest dynamics -- Modelling forest dynamics -- Reproductive ecology and genetic variation -- Forest as habitat -- Towards effective forest conservation.
Includes bibliographical references (pages [379]-430) and indexes.
Mode of access: World Wide Web.
Keywords: Forest ecology; Forest conservation; Electronic books